Practice of economic growth : singapore economics history collection - "Swee, Goh Keng" (London, 1997)
The importance of fast economic growth in developing countries has been an undeniable fact since the early 1970s. Today its significance is even greater as these emerging centers are eagerly sought as bases for economic expansion by developed nations. Singapore, in its rise from a struggling colony to its present status as an economic success, offers a glimpse of the factors that contribute to the growth of a thriving economy. Widely acknowledged as the architect of Singapores economic growth, Dr. Goh Keng Swee describes Singapores experience, which confirms some of the conventional wisdom of growth theory but refutes much of the rest. Examining the social and economic lessons learned by Singapore, Dr. Goh notes that the role of the government and non-economic factors are pivotal to the development of a secure, confident nation. Speaking not as a theoretician, but as a practitioner, he assesses how far theories conform with practice in the real world.
Keywords: Economic development - Singapore